A Novel Type of PD-L1 Inhibitor rU1 snRNPA From Human-Derived Protein Scaffolds Library - Ma, Chuang; Qiao, Sennan; Liu, Zhiyi; Shan, Liang; Liang, Chongyang; Fan, Meiling; Sun, Fei (Frontiers in Oncology, 2021)
Four marketed anti-PD-L1 antibodies almost have severe immune-mediated side effects, the therapeutics effect of anti-PD-L1 chemical inhibitors are not satisfied in clinical trials. Here, we constructed human-derived protein scaffolds library, and screened scaffolds with shape complementary to PD-1 binding domain of PD-L1. RNA binding domain of U1 snRNPA was selected as one of potential binders, because it had the most favorable binding energies with PD-L1, and conformed to pre-established biological criteria for the screening of candidates. Recombinant U1 snRNPA (rU1 snRNPA) in E.coli exhibit anti-cancer activity in melanoma and breast cancer by reactivating tumor-suppressed T-cells in vitro and anti-melanoma activity in vivo. Considering hydrophobic and electrostatic interaction, three residues were mutated on the interface of U1 snRNPA and PD-L1 complex, and ranked variants by PatchDock, A32D showed increased active phenotype. The screening of human-derived protein scaffolds may become the potential development of therapeutic agents.